The battle for good libraries - Mittler, Elmar (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2004)
Libraries are growing and changing service institutions with ever increasing demand of space, equipment and other facilities. Adequate library buildings are therefore in the centre of managerial tasks of librarians. But the construction and reconstruction of buildings for big university or national libraries is rather expensive. That make the programmation and the building process a rather political task with a lot of side effects. Every situation is different, but the experiences at 4 places - Freiburg, Karlsruhe, Heidelberg and Göttingen - show some similarities of the ongoing processes too. These processes for the programmation, decision and realization of successful library building activities will be analysed under 6 major aspects · Situation · Program · Promotion · Partner · Decision Process · Result It should be mentioned, that all libraries in these 4 case studies are financed by the state government: Freiburg, Heidelberg and Göttingen are State Universities. The budget comes via the university from the state government. Best there is a special financing scheme for bigger investment in universities: The federal government pays 50% of the amount needed. The Badische Landesbibliothek Karlsruhe is financed by the state government as well. But there is normally no additional funding by the federal government - that makes it interesting for the States to build combined State and University Libraries like newly the example at Dresden shows. We will see that in Karlsruhe different federal investment resources could be used.